The competences of the graduate teacher: a comparative study of four specialized master’s degrees, from the students’ perspective - Valcazar Montenegro, Edy Esther (2019)
The aim of this study is to demonstrate that significant differences emerge when comparing the evaluation of teachers’ competences from the perspective of the students of the four specialized master’s programs at CENTRUM PUCP, Lima. The applied research was of a non-experimental design, employing comparative description and hypothetical-deductive and quantitative methods. The sample was composed of 143 students from four specialized master’s programs, chosen at random. The information was gathered through a survey, by means of a questionnaire containing 30 items associated with teacher competences. Using the Kruskal-Wallis Test, a meaningful inference was obtained (p-value <0.01) statistically demonstrating the general hypothesis. It can therefore be concluded that significant differences arise when comparing the evaluation of teachers’ competences from the perspective of the students of the four specialized master’s programs.